Carbon Stock Analysis of Waru and Bidara in the Campus Forest of Universitas Negeri Surabaya - Madani, An'nur; Rachmadiarti, Fida (LenteraBio : Berkala Ilmiah Biologi, 2026)
This study evaluated the carbon stock of Hibiscus tiliaceus (Waru) and Ziziphus mauritiana (Bidara) in the UNESA Campus Forest, Surabaya, Indonesia. Its main objective is to analyze the morphological and physiological features that influence their capacity for carbon sequestration, in support of urban reforestation efforts. Non-destructive measurements of chest height diameter (DBH), wood density, and allometric equations were used to estimate biomass and carbon stocks, supplemented by physiological assessments including chlorophyll content and leaf surface. The results of the study showed that Waru showed better morphological characteristics, with an average leaf area of 24,003.28 ± 15,212.06 cm², a stem diameter of 20.26 ± 9.49 cm, and a chlorophyll content of 16.77 ± 6.95 mg/L, producing a biomass of 1923.99 ± 367.03 kg per tree and a carbon stock of 885.04 ± 168.83 kg per tree. In contrast, Bidara has smaller leaves (797.56 ± 72.96 cm²), stem diameter (9.20 ± 4.75 cm), and lower chlorophyll (13.09 ± 5.39 mg/L), with a biomass of 305.37 ± 52.58 kg and a carbon stock of 140.47 ± 24.19 kg. Statistical analysis showed a strong positive correlation between rod diameter and biomass (r = 0.878, p < 0.01) and carbon stock, suggesting that morphological characteristics significantly affect carbon uptake. These findings demonstrate Waru's potential as a strategic urban carbon sink, informing the city's environmental conservation and forestry policies that are aligned with sustainable development goals.